2021
DOI: 10.3390/ijerph18115595
|View full text |Cite
|
Sign up to set email alerts
|

Pain Status and Its Association with Physical Activity, Psychological Stress, and Telework among Japanese Workers with Pain during the COVID-19 Pandemic

Abstract: Changes in working styles and physical activities, and an increase in psychological stress during the coronavirus disease 2019 (COVID-19) pandemic, may have affected pain conditions among workers with pain; however, these associations are still poorly understood. Therefore, we conducted a web-based, cross-sectional study to investigate these changes among Japanese workers suffering from pain. A total of 1941 workers who were aged 20–64 years and suffered from body pain within 4 weeks prior to the study were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 31 publications
1
36
0
2
Order By: Relevance
“…Though this may have influenced the patients’ degree of engagement in physical activity, this variable was not assessed. Activity levels may explain augmented pain during the lockdown (Fallon et al, 2020 ; Yoshimoto et al, 2021 ) and may change in response to care or vice versa. This variable should be monitored and controlled for in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Though this may have influenced the patients’ degree of engagement in physical activity, this variable was not assessed. Activity levels may explain augmented pain during the lockdown (Fallon et al, 2020 ; Yoshimoto et al, 2021 ) and may change in response to care or vice versa. This variable should be monitored and controlled for in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…A few recent studies have reported that work from home is associated with LBP. 5 , 6 , 7 Yoshimoto et al reported an increased risk of LBP among workers who began teleworking and those who increased their frequency of telework during the COVID‐19 pandemic. 5 Another report showed an association between the frequency of telework and the prevalence of LBP.…”
Section: Introductionmentioning
confidence: 99%
“… 5 , 6 , 7 Yoshimoto et al reported an increased risk of LBP among workers who began teleworking and those who increased their frequency of telework during the COVID‐19 pandemic. 5 Another report showed an association between the frequency of telework and the prevalence of LBP. 7 However, one report suggests that telework is not associated with exacerbation of LBP, 8 while another study reported a decrease in musculoskeletal pain including LBP among workers who teleworked in confinement due to the COVID‐19 virus.…”
Section: Introductionmentioning
confidence: 99%
“…Furuichi et al [ 14 ] found that low social support in the workplace increased sick employment (presenteeism) through psychological and physical stress responses and sleep disturbance, using the Work Limitation Questionnaire (WLQ), the Pittsburgh Sleep Quality Index (PSQI), and the Brief Job Stress Questionnaire (BJSQ). Yoshimoto et al [ 15 ] clarified that the percentage of people with enhanced pain was highest among WFH workers with decreased physical activity. According to these results, it is preferable to consider physical activity, psychological aspects, and workstyle to reduce workers’ physical health and stress.…”
Section: Introductionmentioning
confidence: 99%